Transtornos mentais relacionados ao trabalho no Brasil no período de 2006 a 2012 - Brito, Carla de Oliveira (2014)
Objectives: General: estimating the prevalence of mental disorders related to work in Brazil according to sociodemographic, occupational and spatial variables in the period 2006-2012. Specifics: Describe cases of work-related mental disorders in Brazil according to: a) sociodemographic variables (gender, age, education) and b) branch of economic activity) and c) type specific diagnosis in the period 2006-2012 and estimate the prevalence of mental disorders related to work in Brazil, according to characteristics of spatial distribution in the period 2006-2012, considering the Brazilian federative units and regions.Methods: this is a exploratory study was conducted with drawing mixed and temporal series. The cases of work-related mental disorders were obtained in the SINAN and exposed workers was economically active and busy population during the reference period obtained from the IBGE. The occurrence measure was the prevalence rate of TMRT x 1.000.000.The Proportionate Percentage Change (PPV) was used to check the coefficients of variation. Results: there was a large undercount notifications of TMRT SINAN in the period, with each notification SINAN INSS gave 38,5 sickness benefits for workers with the disease. The largest coefficient in TMRT SINAN was in 2011 (7,5 to 1.000.000 workers). The highest proportion was white, young and average level of education women. The hive of activity with highest prevalence was public administration. The Northeast and Southeast regions were the most reported cases of the disease. Conclusion: The results indicate that there is a large underreporting of TMRT the SINAN, however, the prevalence estimates indicate directions to be prioritized by VISAT.